Judiciaries in corrupt societies - Mikael Priks (Center for Economic Studies and ifo Institute (CESifo), 2007)
Recent empirical work shows that judicial dependence can explain high levels of corruption. This paper examines how the dependence of judiciaries influences corruption at different levels of the government in a model where the central government, low-level officials, and the judiciary are corrupt. In the model, the central government sells offices to low-level officials and demands ex-post payments enforced by the judiciary. Because an independent judiciary can rule against the central authority and accept bribes from stealing low-level officials, it reduces corruption at the higher level of government but promotes corruption at the lower level. Therefore, even if highly corrupt, an independent judiciary may reduce total corruption. We provide empirical evidence which is in line with this result.
Keywords: H11; K40; 330; Justiz; Selbstverwaltung; Korruption; Konzession; Public Choice; Spieltheorie; Theorie